Establishment Of Tissue Culture And Hairy Root Production Systems For Solenostemon Scutellarioides (L.) Codd - Thuc, Le Vinh (2004)
In vim propagation of S. scutellarioEdes was canied out by culturing shoot tip explants onto LS, MS and 65 basal medium supplemented with different concentrations of BAP. Comparative analysis of the different types of basal media showed that the LS basal medium supplemented with 8.88 pM BAP was suitable for multiple shoots formation on S. scutellarioides (- 13 shoots/explant). Addition of higher concentrations of BAP (35.5 pM) inhibited multiple shoots and induced abnormal plantlet formation in this species. Culturing shoot tip explants on 65 medium supplemented with 4.52 pM BAP and 2.26 pM 2,4-D produced pink friable callus. On the other hand, culturing leaf explants on MS and 65 media both supplemented with 4.52 pM 2,4-D and 0.46 pM 2,4-D, produced yellowish and grayish friable calli, respectively. Following calli induction, cell suspension culture of S. scu2eIlarirw'des was successfully initiated on MS medium supplemented with 2.26 pM 2,4-D and 0.47 pM kinetin. The cell suspension required only half the amount of 2,443 iii required for calli induction on solid medium (MS + 4.52 pM 2,4-D + 0.46 pM kinetin). In an effort towards achieving genetically stable plant tissue culture material, for the future indudion of valuable secondary metabolite, adventitious roots and hairy roots were induced from S. scufellarioides explants. Quantitative and qualitative assessments of the biomass producing from each of the culture method were analyzed. Adventitious root cultutes in S. sartellarioides leaves were induced by placing explants onto MS basal medium supplemented with different concentrations of auxins (NAA, IBA, IAA) and cytokinin (kinetin). Comparative analysis of the mots enhanced showed that MS medium supplemented with 5.0 pM IBA produced rapidly growing adventitious roots. The presence of cytokinin (kinetin) was inhibiting to adventitious root formation in S. SCUfellarioides. Supplementing MS medium with auxin either IBA or NAA was enough to induce adventitious root formation. Hairy roots of S. scutellarioides were induced by inoculation of leaf explants with A. fiizogenes strains TR 105, LBA 9402,8196 and ATCC 15834. These strains showed different abilities to induce hairy root formation in the leaf explants. Assessment of the plant susceptibility to the different A. rhizogenes strains showed that the strains ATCC 15834, TR 105, LBA 9402, and 81 96 produced 56.3%, 25.5%, 21.5%, and 13.8% transformation efficiencies, respectively. Acetosyringone was found to be useful for enhancement of hairy root production in S. s c u t d I 8 ~